2014
DOI: 10.1007/s10640-014-9824-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmentally Friendly Innovations on Value Added

Abstract: While recent literature has focused on explaining the determinants of green innovations, it is not well understood how such innovations affect performance. To analyse the relationship between green innovation and performance, new industry-level panel data were exploited: these include 12 OECD countries, the whole manufacturing sector and a period of 30 years. The results show that green inventions are U-shape related to performance. However, the turning point is quite high and hence only relevant for a few ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 38 publications
(25 reference statements)
2
36
0
Order By: Relevance
“…In specification V, however, when we also incorporate the quadratic term, the breadth variable becomes negative and significant, and the quadratic term positive and significant, which suggests that the wider array of eco-strategies influences firm performance more than proportionality. The relationship between firm growth and the number of eco-strategies carried out by firms is U-shaped, in line with the findings of Soltmann et al [29] using industry-level data. This implies that when the number of eco-strategies undertaken is low, this has a negative impact on firm performance.…”
Section: (I) (Ii) (Iii) (Iv) (V)supporting
confidence: 89%
See 1 more Smart Citation
“…In specification V, however, when we also incorporate the quadratic term, the breadth variable becomes negative and significant, and the quadratic term positive and significant, which suggests that the wider array of eco-strategies influences firm performance more than proportionality. The relationship between firm growth and the number of eco-strategies carried out by firms is U-shaped, in line with the findings of Soltmann et al [29] using industry-level data. This implies that when the number of eco-strategies undertaken is low, this has a negative impact on firm performance.…”
Section: (I) (Ii) (Iii) (Iv) (V)supporting
confidence: 89%
“…Using industry-level data from 12 OECD countries, Soltmann et al [29] shows that the general relationship between the intensity of green inventions and performance is U-shaped. They concluded that the turning point is quite high and consequently only relevant for a few industries.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…It can also be observed that consumers are more willing to pay such a premium for commodities rather than for more complex systems. The latter is explained by observing that an increasing level of green inventions is found to negatively affect performances of the system [38], following U-shaped relationship. Several studies [39,40] further show that the decision of buying green and paying a premium price is mainly influenced by social and cultural norms, and that individuals are more sensitive towards social sustainability aspects that towards environmental sustainability [41].…”
Section: Metalevel Contributions and Challengesmentioning
confidence: 99%
“…In addition to the extended model results above, we examine the robustness of our main findings with a number of alternative specifications and sensitivity checks, which are typically encountered in comparable settings: Specifically, we assess the impact of allowing time‐varying organizational variables (in Section ; cf., e.g., Arvanitis et al, ), separate inclusion of interaction terms (in Section ; cf., e.g., Arvanitis et al, ; Hollenstein & Stucki, ), individual subcomponents of organizational capital components (in Section ; cf., e.g., Stucki & Woerter, ), usage of direct measures for IT (in Section ; cf., e.g., Bloom et al, ), and finally assess differences over time (in Section ; cf., e.g., Soltman et al, ). The following tests are all based on our main model specification provided in Column 3 of Table , which simultaneously includes both computer and intranet use and controls for industry‐time fixed effects as well as firm fixed effects.…”
Section: Estimation Resultsmentioning
confidence: 99%